THERMODYNAMICS OF POINT DEFECTS AND THEIR INFLUENCE ON PHYSICAL AND CHEMICAL PROPERTIES OF CRYSTALS CADMIUM TELLURIDE (REVIEW) - Фреїк, Дмитро Михайлович; Горічок, Ігор Володимирович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The analysis of basic types own defects points is resulted in the cadmium telluride crystals and their power parameters – created energy, ionization energy, frequency change atoms vibrations in surroundings defects. It is set that difference between experimental and theoretical data is the main reason of existent vagueness during interpretation physical and chemical properties of cadmium telluride.